PENERAPAN MODEL PEMBELAJARAN EXPERIENTAL LEARNING UNTUK MENINGKATKAN PEMAHAMAN KONSEP PADA MATERI CAHAYA DAN SIFAT-SIFATNYA DI KELAS V UPTD SD NEGERI 5 JULI - Rahmawati, Ayu; Fatma Zuhra; Nanda Safarati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve students' conceptual understanding of light and its properties through the application of the Experiential Learning model in Grade V at UPTD SD Negeri 5 Juli. This research is a Classroom Action Research (CAR) conducted in two cycles, comprising planning, acting, observing, and reflecting stages. The subjects consisted of 24 students. Data were collected using written test instruments, teacher and student activity observation sheets, and student response questionnaires.The results showed a consistent graph of improvement in learning quality. In Cycle I Action 1, the teacher activity percentage was 84.28% and student activity was 85.56%, which increased in Action 2 to 86% for teacher activity and 86% for student activity. Meanwhile, in Cycle II Action 1, teacher activity reached 90% and student activity was 89.28%, further increasing in Action 2 to 95.33% for teacher activity and 92.66% for student activity, both categorized as excellent. Regarding the classical mastery of conceptual understanding, Cycle I only reached 54.17% (13 out of 24 students). Following improvements in Cycle II, a significant increase occurred, with classical mastery reaching 91.7% (22 out of 24 students). These results prove that the predetermined success indicator of 80% was exceeded. Based on these findings, it can be concluded that the implementation of the Experiential Learning model is effective in enhancing Grade V students conceptual understanding of light and its properties in IPAS at UPTD SD Negeri 5 Juli.